First and Second Language Acquisition in German Children Attending a Kindergarten Immersion Program: A Combined Longitudinal and Cross‐Sectional Study. Issue 2 (17th February 2016) - Bergström, Kirstin; Klatte, Maria; Steinbrink, Claudia; Lachmann, Thomas
Abstract : This study investigated first (L1) and second (L2) language acquisition in two age‐matched groups of 2‐ to 6‐year‐old kindergarten children over the course of 2.5 years. The immersion group participated in a partial English immersion program whereas the conventional instruction group received a conventional L2 course (30 minutes per week); the groups were comparable with respect to control variables (e.g., socioeconomic status). L1 and L2 competencies were assessed at four time points (pretest and three posttests). No detrimental effects of immersion on L1 development were found. Concerning L2 receptive skills, the immersion group outperformed the conventional instruction group in each posttest. Contact quality and quantity were found to relate to L2 acquisition through immersion. Immersion appears to be a successful method for early L2 learning; it fosters L2 receptive skills without any cost for the L1.